FRI0132 A multi-biomarker disease activity score (the vectra DA algorithm score) reflects clinical remission for rheumatoid arthritis (RA) in the best study. (23rd January 2014) - Hirata, S.; Dirven, L.; Cavet, G.; Centola, M.; Lems, W.F.; Tanaka, Y.; Huizinga, T.W.; Allaart, C.F.
Abstract : Background: The multi-biomarker disease activity (MBDA) score has been reported as a novel composite disease activity index for rheumatoid arthritis (RA). To date, we have reported a good correlation of the MBDA score to DAS28, HAQ, and mTSS in the BeSt study population. However, many aspects of its utility in clinical practice are still to be elucidated. Many rheumatologists favor alternative disease activity indices such as CDAI and SDAI, and the identification of patients in remission is of great interest in current rheumatology. Objectives: To determine whether the MBDA score reflects clinical disease activity as assessed by CDAI or SDAI, and to clarify the relationship between MBDA score remission and clinical remission. Methods: A total of 125 RA patients from the BeSt study were studied. Clinical data and serum samples were available from 179 visits, 91 at baseline (BL) and 88 at year 1. The MBDA algorithm combines 12 serum biomarkers (VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, MMP-1, MMP-3, YKL-40, Leptin, Resistin, CRP, SAA) into a single score from 1-100 and is used in Vectra™ DA, a multi-biomarker blood test for RA disease activity. The biomarkers were measured in each serum sample using quantitative multiplex immunoassays, and the concentrations were used as input to the MBDA algorithm to calculate score. MBDA disease activity categories were defined as high (HDA: >44), moderate (MDA: ≤44), low (LDA: ≤29), and remission (REM: ≤25). The association between MBDA and DAS28/SDAI/CDAI were evaluated by Spearman's rank correlation coefficients (Spearman's ρ). Agreement in disease activity categories (REM/LDA/MDA or HDA) between MBDA and DAS28/CDAI/SDAI was assessed by Pearson's chi-square test. Agreement of REM in MBDA and REM in DAS28/CDAI/SDAI/ACR/EULAR Boolean definition were analyzed by area under the receiver operating characteristic curve (AUROC). All reported p-values are two sided and p-values <0.05 were considered significant. Results: The MBDA score was significantly correlated to CDAI (ρ=0.56, p<0.0001), and SDAI (ρ=0.67, p<0.0001), similar to its correlation with DAS28 (ρ=0.66, p<0.0001). Disease activity with MBDA had similar distribution with DAS28, CDAI, and SDAI (p<0.0001 in all cases). The proportions of patients in remission by various criteria were 17% by MBDA score, 21% by DAS28, 12% by CDAI, 11% by SDAI, and 9% by ACR/EULAR Boolean criteria. MBDA remission showed good agreement with DAS28-REM (AUROC=0.84, p<0.0001), CDAI-REM, (AUROC=0.78, p=0.0040), SDAI-REM (AUROC=0.80, p=0.0009) and Boolean-REM (AUROC=0.83, p<0.0001), respectively. Conclusions: The MBDA score measures clinical disease activity as assessed by several different clinical indices. A molecular remission state defined by the MBDA score is associated with clinical remission definitions and may offer complementary information about quiescence of underlying biological disease pathways. Disclosure of Interest: S. Hirata: None Declared, L. Dirven: None Declared, G. Cavet Employee of: Crescendo Bioscience Inc., M. Centola: None Declared, W. Lems: None Declared, Y. Tanaka Grant/Research support from: Bristol-Myers Squibb, Mitsubishi-Tanabe, MSD, Takeda Industrial, Astellas, Eisai, Chugai, Pfizer and Daiichi-Sankyo, Consultant for: Chugai, Mitsubishi-Tanabe, Eisai, Pfizer, Abbott Immunology, Janssen, Takeda Industrial, Astra-Zeneca, Astellas, Asahi-kasei and GlaxoSmithKline, Speakers Bureau: Chugai, Mitsubishi-Tanabe, Eisai, Pfizer, Abbott Immunology, Janssen, Takeda Industrial, Astra-Zeneca, Astellas, Asahi-kasei and GlaxoSmithKline, T. Huizinga Consultant for: Schering Plough, UCB, Bristol Myers Squibb, Biotest AG, Wyeth/Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Axis-Shield diagnostics, C. Allaart Speakers Bureau: Schering Plough, Mitsubishi Tanabe Pharma, UCB, Abbott and Pfizer